A Work-Integrated Learning Framework: the what, where and how of evaluating WIL - Karen Young; Sophie McKenzie; Jill Thomas (Journal of Teaching and Learning for Graduate Employability)
Through a case study at Deakin University, we present our approach for evaluating Work-Integrated Learning (WIL) during a pilot of a WIL Evaluation Framework (WEF). This paper focuses on our approaches and decisions relating to what, where and how to evaluate WIL, offering considerations for a sector-wide approach to WIL evaluation more generally. The findings from the pilot inform ongoing institution-specific WIL evaluation projects. We anticipate that our study will provide insight into the comprehensive processes involved in WIL evaluation, and the impact findings can make to inform WIL and employability strategies to supplement current sector-wide discussions on WIL indictors and measures of success for graduate outcomes.